Facteurs a priori et in situ de l’engagement des étudiants dans les forums de discussion des MOOC - Yannick Stéphane Nleme Ze; Gaëlle Molinari (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This mixed instrumental case study explores the factors of engagement in MOOC discussion forums as perceived by students at the University of Geneva. To this end, data from 127 questionnaire responses and 11 semi-structured interviews were analysed through the lens of self-determination theory and its motives for engagement, models of motivational dynamics, acceptability and in situ acceptance of technologies. The results have enabled the development of a model that shows how11 factors a priori and 23 in situ affect the students’ engagement in the forums.